Al-Ȃtsȃr al-Mutarattibah ‘Ȃla PERPPU (Lawȃih al-Hukûmiyyah al-Badaliyyah) min al-Munazhzhamȃt al-Mujtama’iyyah raqm 2 li ‘ȃm 2017 dlidda wujûd hizb al-Tahrîr Indûnîsiyȃ min Manzhûr saddi al-dzarî’ah - Abdul Jalil; Muhammad Taufiq (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2019)
The perspective of Islamic constitutional law, The Unitary State of the Republic of Indonesia is in harmony with the principles of Islamic state administration, because the system of government implemented has embraced the principles of Islamic constitution such as; al-Musâwah (equality), al-‘Adâlah (justice), al-Syûrâ (democration), al-Hurriyyah (freedom). The principle is contained in the five precepts of the Panacaila. HTI's efforts to establish a khilafah government according to its version in the Unitary Republic of Indonesia can disrupt the system, basis and philosophy of the State, can result in national disintegration, can eliminate religious tolerance which is substantially the principle in Islamic state administration. The birth of Perppu Number 2 of 2107 has implications for the closure of opportunities (Sadd al-Dzarîah) Community Organizations that have teachings or understandings contrary to Pancasila grow within the Unitary State of the Republic of Indonesia and HTI becomes a prohibited organization living in Indonesia. According to the consequentialist approach, the existence of HTI threatens the sovereignty of the State, so that being included in the category of levels of sadd al-dzarîah which has the effect of causing harm and danger therefore, to avoid alternative declarations dissolving HTI is the right choice that must be put forward.